ANALISIS HUKUM CRYTOCURRENCY KAJIAN FIKIH DAN FATWA-FATWA DI LUAR NEGERI (IAIN Tulungagung, 2023)
Cryptocurrency is the first application of Blockchain technology, but the potential of this technology is not limited to the monetary system and its widespread adoption is still a topic of debate around the world which causes many countries are investigating this cryptocurrency. Here the author attempts to assess crypto assets based on studies and fiqh fatwas abroad. In this study the authors use normative legal research, normative legal research is intended to provide legal arguments as a basis for determining whether an event is right or wrong. To analyze existing theories, this study uses a conceptual approach to analyze existing theories so that solutions to legal problems can be found. The results in this study are that there are two thoughts, the first school of thought argues that cryptocurrencies can be used for payments, remittances, and deposit assets as long as users know in detail the types of cryptocurrencies, their main characteristics and the risks associated with them. Due to the lack of a clear legal framework for digital currencies and the substantial harm involved for individuals and countries, second opinions are prohibited in the eyes of the Shari'ah due to the excessive risk to individuals, countries and the absence of a clear legal umbrella regarding these cryptocurrencies.